Cucurbit[n]uril (n = 6, 7) Based Carbon-Gold Hybrids with Peroxidase-Like Activity - Liangfeng Zhang; Yan Zeng; Simin Liu; Feng Liang (Nanomaterials, 2018)
Despite the combination of molecular recognition and local electric field enhancement endowing cucurbit[n]uril-capped metallic nanoparticles, indicating great potential in a variety of areas, prior work has paid little attention to carbonizing cucurbit[n]uril on the surface of gold nanoparticles, which may propose new carbon-gold hybrid materials with interesting applications. In this work, we developed a simple and cost-effective method to prepare carbon-gold hybrids by carbonizing cucurbit[n]uril modified gold nanoparticles. The as-prepared cucurbit[n]uril based carbon and carbon-gold hybrid materials have shown to possess peroxidase-like activity. All cucurbit[n]uril based nanomaterials exhibited high catalytic activity over a pH range 2–6 and more tolerant to high temperature (up to 60 °C) when compared to natural horseradish peroxidase.